Application of corrosion-resistant glass fiber reinforced plastic extraction tank in recycling of metal from waste lithium battery

CN122918324APending Publication Date: 2026-10-16LIANYUNGANG BRIGHT-GOLDEN FRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610975977.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

现有玻璃钢萃取槽如公开号为CN2533934Y、CN202898488U的专利,针对的是稀土分离或铜湿法冶炼介质,其腐蚀环境与废旧锂电池浸出液存在本质差异

Benefits of technology

三层复合内衬层显著提升了耐氯氟复合腐蚀性能,通过PTFE微粉的疏氟疏氯特性和纳米SiO2的阻隔增强效应,其对60~80℃下浓度不高于5000ppm的F-及不高于10000ppm的Cl-的耐受能力,较对比文件公开号为CN2533934Y的专利中的常规玻璃钢提升3倍以上;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918324A_ABST
    Figure CN122918324A_ABST
Patent Text Reader

Abstract

The application discloses application of a corrosion-resistant glass fiber reinforced plastic extraction tank in metal recovery from waste lithium batteries, and the waste lithium batteries are crushed, sorted and subjected to acid leaching to obtain a leaching liquor; the leaching liquor is subjected to extraction separation of valuable metals in the extraction tank; and metal salt solution is obtained through reverse extraction of the loaded organic phase. The extraction tank is of a whole laminated glass fiber reinforced plastic structure, is internally provided with a mixing chamber and a clarification chamber, is provided with a reinforcing rib on an outer wall, and is internally provided with three layers of composite lining layers, wherein a bottom layer is a phenolic vinyl ester resin layer, a middle layer is an epoxy vinyl ester resin layer containing nano SiO2, and a surface layer is an epoxy vinyl ester resin layer containing PTFE micro powder. The application is optimized in design in view of specific corrosion media in the recovery of waste lithium batteries, and solves the technical problem that the existing glass fiber reinforced plastic extraction tank is prone to peeling and corrosion leakage in a fluorine-chlorine strong acid system, and is especially suitable for large-scale hydrometallurgical extraction equipment, and belongs to the technical field of solid waste comprehensive utilization and metal waste processing in the resource recycling industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of resource recycling technology for waste lithium batteries, specifically relating to the application of a corrosion-resistant fiberglass extraction tank in the metal recycling of waste lithium batteries. This extraction tank, as a specialized environmental protection equipment in the processing of metal waste, is suitable for extracting and separating valuable metals such as cobalt, nickel, manganese, and lithium from the leachate of waste lithium batteries. Background Technology

[0002] Used lithium batteries contain large amounts of valuable metals such as cobalt, nickel, manganese, and lithium. According to the "Law on the Prevention and Control of Environmental Pollution by Solid Waste," used lithium batteries are classified as recyclable solid waste. Processing them into metal scrap to achieve resource recycling is the core of the resource recycling industry.

[0003] With the rapid development of the new energy vehicle industry, the number of waste lithium batteries has increased dramatically. Waste lithium batteries contain large amounts of valuable metals such as cobalt, nickel, manganese, and lithium, possessing extremely high recycling value. The use of hydrometallurgical processes to recover valuable metals from waste lithium batteries has become the mainstream technical approach in this field. Solvent extraction is a key step in separating and purifying valuable metals. In a typical process, P204 (di-(2-ethylhexyl)phosphoric acid) is usually used as the extractant to remove impurities such as iron, aluminum, zinc, and manganese from the leachate. Then, P507 (2-ethylhexylphosphonic acid mono-2-ethylhexyl ester) is used for selective extraction and separation of cobalt and nickel under pH conditions of 4-5.5, achieving stepwise recovery of multiple metals. Currently, P507 is widely recognized as an excellent extractant for separating Co(II) / Ni(II), and its separation performance is closely related to the acidity of the extractant and the stability of the tetrahedral Co(II) complex in the organic phase of the extraction system.

[0004] Fiberglass reinforced plastic (FRP) is widely used in hydrometallurgical extraction equipment due to its excellent corrosion resistance and good structural strength. Patent CN2533934Y discloses an improved extraction tank for rare earth separation, featuring an extraction tank integrally laminated with FRP. This extraction tank has a flanged reinforcing edge around its upper perimeter, reinforcing ribs around its central perimeter, and reinforcing ribs at the top of each longitudinal and transverse partition plate. The peripheral and bottom corners have an arc-shaped structure. This technical solution has advantages such as good overall rigidity, high structural strength, temperature and corrosion resistance, resistance to deformation, and long service life, making it particularly suitable for manufacturing large extraction tanks. Patent CN202898488U discloses a reinforced FRP extraction clarification tank, which has reinforcing ribs on the outer wall of the FRP tank, and FRP columns arranged longitudinally and transversely inside the tank. The height of the columns is the same as the height of the tank, and longitudinal and transverse FRP tie plates are arranged along the column array at the top of the tank. The improvement of this patent lies in the arrangement of right-angled reinforcing plates at the joints of the four side plates and the bottom plate within the tank, thus solving the problem of stress concentration and easy cracking and leakage at the joints. It is mainly applied to copper hydrometallurgical production. Patent CN202898487U, a pure fiberglass extraction and clarification tank, incorporates fiberglass reinforcing hoops and vertical reinforcing ribs on the outer wall of the tank to address the frequent corrosion and leakage issues associated with steel structure frames combined with fiberglass tanks. Patent CN114892005A, a method for comprehensive recycling of waste lithium batteries, discloses a complete process flow for comprehensive recycling of waste lithium batteries, including steps such as crushing → slurry electrolysis → sieving → filtration → oil removal → copper removal → iron removal → impurity removal → displacement → extraction → acid adjustment → precipitation → MVR + crystallization. Patent CN220914333U, an extraction device for wet recycling of waste lithium batteries, relates to the technical field of waste battery recycling equipment.

[0005] Although existing technologies include patents for fiberglass extraction tanks (publication numbers CN2533934Y and CN202898488U) and waste lithium battery recycling processes (publication numbers CN114892005A and CN220914333U), the combination of the two has the following shortcomings: (1) The essential differences between corrosive media have not been fully understood. The leachate from spent lithium batteries is a strongly acidic system, typically with a pH of 1.0 to 2.0, and contains high concentrations of fluoride and chloride ions. This is because LiPF6 in the lithium battery electrolyte hydrolyzes during leaching to produce HF, and the residual PVDF binder in the cathode material also releases fluoride ions during subsequent processing. Existing fiberglass extraction tanks, such as those published in patents CN2533934Y and CN202898488U, are designed for rare earth separation or copper hydrometallurgical media, whose corrosive environment differs fundamentally from that of spent lithium battery leachate.

[0006] (2) Differences in acid mist corrosion environment Existing technologies, such as the patent with publication number CN202898488U, indicate that the main media in copper hydrometallurgical extraction workshops are sulfuric acid, 260# solvent oil, and cobalt sulfate, which cause severe vapor phase corrosion. In contrast, the vapor phase corrosion in waste lithium battery recycling extraction workshops, in addition to the aforementioned components, also contains volatile acidic gases such as HF and HCl, resulting in different corrosion mechanisms on the upper flange and outer wall of the fiberglass tank.

[0007] (3) Lack of inner lining protection technology A search revealed that existing FRP extraction tank patents, such as those with publication numbers CN2533934Y, CN202898488U, and CN202898487U, do not feature a dedicated functional lining for the corrosive media in waste lithium battery recycling, nor do they provide any technical guidance on optimizing resin type and layup structure based on media composition.

[0008] (4) Technological gaps in application scenarios The existing technology does not provide any technical insights into applying fiberglass extraction tanks, which are specifically optimized for resistance to chlorine and fluorine corrosion, to the specific process conditions of metal recycling from waste lithium batteries, such as specific pH ranges, temperature conditions, and extractant system combinations. Summary of the Invention

[0009] The purpose of this invention is to address the requirement that extraction equipment in the wet recycling process of waste lithium batteries must withstand H2O. + F - Cl - To address the specific requirements of complex corrosive media and the shortcomings of existing FRP extraction tank technologies that are not optimized for this particular corrosive environment, this invention provides a corrosion-resistant FRP extraction tank for the recycling of metals from waste lithium batteries. This invention applies the extraction tank to the extraction and separation stage of wet recycling of waste lithium batteries. It can withstand the special requirements of complex corrosive media containing H+, F-, and Cl-. In a waste lithium battery leachate system containing 1000~5000 ppm F-, 2000~10000 ppm Cl-, and pH 1.0~2.0, the service life of the extraction tank of this invention is more than three times longer than that of conventional bisphenol A type epoxy vinyl ester resin FRP extraction tanks.

[0010] To achieve the above objectives, the technical solution of this invention is to design a corrosion-resistant fiberglass extraction tank for the recycling of metals from waste lithium batteries, comprising the following steps: (1) The waste lithium batteries are crushed, sorted and acid-leached to obtain acidic leachate; (2) The leachate is solvent extracted in the corrosion-resistant fiberglass extraction tank to extract and separate valuable metal elements; (3) The supported organic phase was back-extracted to obtain a metal salt solution; The corrosion-resistant fiberglass extraction tank comprises a tank body made of integral laminated fiberglass material. The tank body contains a mixing chamber and a clarification chamber, separated by a partition plate. The corners of the tank body feature rounded transitions, and the outer wall is reinforced with ribs. The surface of the tank body in contact with the corrosive medium is equipped with a three-layer composite functional liner, consisting of a bottom layer, an intermediate layer, and a top layer, sequentially composited from the inside out. The bottom layer is a phenolic vinyl ester resin fiberglass layer, the intermediate layer is a bisphenol A type epoxy vinyl ester resin fiberglass layer containing nano-SiO2, and the top layer is a bisphenol A type epoxy vinyl ester resin fiberglass layer containing PTFE micropowder. After the three composite functional liner layers are laid sequentially, a stepped heating and curing process is used: first, holding at 80℃ for 2 hours, then raising the temperature to 100℃ and holding for 3 hours, and finally raising the temperature to 120℃ and holding for 4 hours, forming a chemically bonded transition layer between each layer. The formation of this chemically bonded transition layer during the stepped heating and curing process inhibits interfacial stress cracking.

[0011] A further technical solution involves a bottom layer thickness of 2-3 mm, a middle layer thickness of 3-5 mm, a top layer thickness of 1-2 mm, and a total thickness of 6-10 mm. The nano-SiO2 particles have a diameter of 20-50 nm and are added at 5%-10% of the resin mass. The PTFE micropowder particles have a diameter ≤10 μm, are surface-modified with a silane coupling agent, and are added at 3%-8% of the resin mass. In the structural design of the extraction tank, the total wall thickness is typically controlled within the range of 15 mm to 28 mm, preferably 20 mm to 24 mm. The fiberglass structure layer has a thickness of 9-22 mm, and a three-layer composite functional liner with a total thickness of 6-10 mm is installed on the inner side. The total thickness of the liner is generally set to 6 mm to 10 mm, with 8 mm being a preferred choice. To improve the wear resistance and corrosion resistance of the material, the addition amount of nano-SiO2 should be controlled at 5%-10%, preferably 7%; the addition amount of PTFE micropowder should be controlled at 3%-8%, preferably 5%. Regarding the dimensions of each tank compartment, the length can be set to 1000mm–2000mm, the width to 800mm–1500mm, and the height to 1000mm–2500mm. An optimal combination of dimensions is 2000mm in length, 1500mm in width, and 1800mm in height. Appropriate selection of these parameters helps to ensure structural strength while also considering corrosion resistance, fabrication feasibility, and operational stability.

[0012] A further technical solution is to use a stepped heating and curing process after the three-layer composite functional lining is laid: first, cure at 80℃ for 2 hours, then heat to 100℃ for 3 hours, and finally heat to 120℃ for 4 hours, so that a chemically bonded transition layer is formed between each layer.

[0013] A further technical solution involves a flange sealing system at the upper flange of the tank, including a sealing gasket and an acid mist baffle. The sealing gasket is placed on the flange sealing surface to achieve initial sealing of the flange connection surface. The acid mist baffle has a double-layer structure: an inner layer of phenolic vinyl ester resin fiberglass and an outer layer of acid-resistant rubber sealing layer, which is fixed to the inner layer surface by adhesive bonding. The acid mist baffle extends from the upper flange surface of the tank, and has a double-layer structure: an inner layer of phenolic vinyl ester resin fiberglass and an outer layer of acid-resistant rubber sealing layer, preventing gaseous corrosive media from penetrating into the flange connection surface.

[0014] A further technical solution is that the pH value of the leachate in step (2) is 1.0~2.0, and it contains F. - 1000~5000ppm, Cl - 2000~10000ppm; the solvent extraction uses one or more of P204 or P507 extractants, and the operating temperature during the extraction process is 15~45℃.

[0015] A further technical solution is that the valuable metal element is selected from one or more of cobalt, nickel, manganese, and lithium.

[0016] A further technical solution is that an adjustable light phase weir is provided at the top of the clarification chamber and a heavy phase outlet is provided at the bottom; a stirring device is provided in the mixing chamber, and the surface of the stirring shaft and impeller is covered with a three-layer composite functional inner lining layer that is the same as the inner lining layer of the tank.

[0017] The step-heat curing process of this invention works on the following mechanism: the coefficient of thermal expansion of phenolic vinyl ester resin is 25~30×10⁻⁶. -6 At / ℃, the coefficient of thermal expansion of bisphenol A type epoxy vinyl ester resin is 50~60×10⁻⁶. -6 / ℃. When the bottom layer cures first at 80℃, some of the hydroxymethyl active groups in the bottom layer resin remain at the interface and are not fully cross-linked. Subsequently, when the intermediate layer is cured at 100℃, the epoxy / hydroxyl groups of the epoxy resin in the intermediate layer undergo a ring-opening etherification reaction with the hydroxymethyl groups remaining at the bottom layer interface, forming a COC ether bond chemically bonded transition layer. Similarly, interfacial chemical bonding also occurs between the intermediate layer and the top layer during the temperature rise from 100℃ to 120℃. It is well known in the art that differences in the coefficient of thermal expansion are a common cause of interlayer cracking in multilayer fiberglass structures. This invention takes the opposite approach, using a stepped temperature rise and curing process to allow the three-layer composite functional liner to complete curing and shrinkage sequentially within their respective curing temperature windows. On the one hand, this promotes the reaction of active groups at the interfaces of adjacent layers, forming a chemically bonded transition layer and fundamentally inhibiting interfacial delamination. On the other hand, through a reasonable thickness ratio design, the interlayer thermal stress is controlled within the elastic range, achieving structural reinforcement. The synergistic effect of the above processes not only solves the problem of easy delamination of multilayer fiberglass liners but also significantly improves the long-term service reliability of the tank in fluorinated chlorine-containing strong acid media.

[0018] The extraction tank of this invention is applied to the following process steps in the recycling of metals from waste lithium batteries: (1) Pretreatment leaching: The positive electrode active material obtained by crushing and sorting waste lithium batteries is subjected to reduction acid leaching using a sulfuric acid + hydrogen peroxide system. Among them, hydrogen peroxide is used as a reducing agent to reduce the high-valence metal ions such as cobalt, nickel, and manganese in the positive electrode active material to low-valence states, so that sulfuric acid can dissolve them. After solid-liquid separation, the leachate enters the extraction section for separation and purification of valuable metals, to obtain an acidic leachate containing Co²⁺, Ni²⁺, Mn²⁺, and Li⁺, with pH=1.0~2.0, F⁻ concentration of 1000~5000ppm, and Cl⁻ concentration of 2000~10000ppm. (2) P204 extraction for impurity removal: P204 (diisooctyl phosphate) extractant is used with a saponification rate of 60%~70% to extract and remove impurities such as Zn²⁺, Ca²⁺, and Mg²⁺ from the leachate; (3) P507 extraction to separate cobalt and nickel: P507 (2-ethylhexylphosphonic acid mono-2-ethylhexyl ester) extractant, pH=4.0~5.5, is used to extract and separate cobalt and nickel; (4) Back-extraction and product preparation: The loaded organic phase is back-extracted to obtain solutions of cobalt sulfate, nickel sulfate and other substances, which are then used to prepare battery-grade precursor materials.

[0019] The advantages and beneficial effects of this invention are as follows: The three-layer composite lining significantly improves resistance to chlorine-fluorine composite corrosion. Through the fluorine- and chlorine-repellent properties of PTFE micropowder and the barrier-reinforcing effect of nano-SiO2, it effectively resists fluorine and chlorine corrosion at concentrations not exceeding 5000 ppm at 60–80°C. - and Cl not exceeding 10000 ppm- Its durability is more than 3 times higher than that of conventional fiberglass in the patent with publication number CN2533934Y; The interlayer bonding strength of the three-layer inner lining is significantly improved. The gradient curing process forms a chemically bonded transition layer between each layer, effectively avoiding the interface cracking problem caused by the difference in the thermal expansion coefficient between layers in conventional multilayer composite structures. The three-layer composite inner lining significantly enhances the protection against vapor phase corrosion. Its upper flange acid mist baffle structure solves the problem of easy corrosion and leakage at the flange connection surface of the fiberglass extraction tank in the HF and HCl vapor phase environment described in the patent with publication number CN2533934Y. This invention fills a technological gap regarding optimized fiberglass extraction tanks and their specific applications for recycling waste lithium batteries in corrosive media, technologies not disclosed in existing technologies. Compared to existing technologies, this invention significantly improves the long-term reliability of fiberglass extraction tanks in highly acidic media containing high concentrations of F⁻ and Cl⁻ through the synergistic effect of a three-layer composite lining structure and a stepped curing process, thus filling a technological gap in dedicated extraction equipment for waste lithium battery recycling. This technical solution is particularly suitable for recycling waste power batteries containing LiPF6 electrolyte.

[0020] Compared to the prior art patent CN2533934Y, this invention utilizes a stepped temperature curing process to form a chemically bonded transition layer at the interface of the three-layer inner liner. The prior art patent does not disclose this process; its multi-layer structure employs a conventional co-curing process, where different resin layers cure simultaneously at the same temperature. Differences in thermal expansion lead to interlayer stress accumulation and interface cracking. Testing according to GB / T 1458 shows that the interlayer shear strength of this invention is 88% higher than that of the conventional co-curing process. After 200 cycles of thermal cycling from -40℃ to 80℃, the interlayer peel strength remains at 3.9 kN / m, compared to 0.5 kN / m in the conventional process, indicating successful peeling. This demonstrates the effective suppression of interlayer stress by the chemically bonded transition layer. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of an application embodiment of the corrosion-resistant fiberglass extraction tank of the present invention in the recycling of metals from waste lithium batteries; Figure 2 This is a partial schematic diagram of the upper flange of the extraction tank in Embodiment 4 of the present invention.

[0022] In the diagram: 1-Tank body; 2-Mixing chamber; 3-Clarification chamber; 4-Light phase weir; 5-Dense phase outlet; 6-Agitator; 7-Bridging plate; 8-Reinforcing rib; 9-Circular arc corner; 10-Upper flange; 11-Compensation tank; 12-Circular arc; 13-Acid mist baffle; 14-Soft acid-resistant rubber layer; 15-Hard PTFE annular protrusion. Detailed Implementation

[0023] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.

[0024] Example 1: As Figure 1 As shown (for ease of illustration), Figure 1 (Only one cell is shown). This invention relates to the application of a corrosion-resistant fiberglass extraction tank in the recycling of metals from waste lithium batteries. This embodiment provides a corrosion-resistant fiberglass extraction tank for wet recycling of waste lithium batteries, with the following specific structure: The overall dimensions of the tank body 1 are 6000mm (length) × 3000mm (width) × 2500mm (height), divided into 6 cells. The tank body matrix material is alkali-free glass fiber reinforced bisphenol A epoxy vinyl ester resin fiberglass. The structural layer resin is bisphenol A epoxy vinyl ester resin; the glass fiber reinforcement material is alkali-free glass fiber cloth with a unit area mass of 600g / m²; the bottom layer resin is phenolic vinyl ester resin; the middle and top layer resins are bisphenol A epoxy vinyl ester resin; the reinforcement material is alkali-free glass fiber cloth with a unit area mass of 600g / m²; nano-SiO2 with a particle size of 30nm is added at 7%; PTFE micro powder with a particle size of 5μm is added at 5%. The PTFE micro powder is added to the resin system after surface modification treatment with a silane coupling agent. The tank 1 contains a mixing chamber 2 and a clarification chamber 3, separated by a partition plate 7. The corners of the tank feature a rounded transition structure (rounded corner 9), and the outer wall is reinforced with ribs 8. An adjustable light phase weir 4 is located at the top of the clarification chamber 3, and a heavy phase outlet 5 is located at the bottom. A stirring device 6 is installed in the mixing chamber, with the stirring shaft and impeller surface covered by a three-layer composite functional inner lining layer identical to the tank's inner lining. The upper flange of the tank 1 is equipped with a flange sealing system, including a gasket and an acid mist baffle 13. The gasket is placed on the flange sealing surface to achieve initial sealing of the flange connection surface. The acid mist baffle 13 has a double-layer structure: an inner layer of phenolic vinyl ester resin fiberglass and an outer layer of acid-resistant rubber sealing layer, which is fixed to the inner layer surface by adhesive bonding.

[0025] The preparation process of the inner lining layer is as follows: the bottom layer is prepared by coating the surface of the fiberglass structure layer with phenolic vinyl ester resin adhesive, attaching two layers of fiberglass surface mat, curing at room temperature for 12 hours, and then performing post-curing treatment according to a stepped temperature increase process; the middle layer is prepared by coating the surface of the middle layer with epoxy vinyl ester resin adhesive containing nano-SiO2, attaching three layers of fiberglass cloth, curing at room temperature for 12 hours, and then performing post-curing treatment according to a stepped temperature increase process; the top layer is prepared by coating the surface of the middle layer with epoxy vinyl ester resin adhesive containing PTFE micro powder, attaching two layers of fiberglass surface mat, curing at room temperature for 12 hours, and after the three composite functional inner lining layers are laid in sequence, the whole is treated with a stepped temperature increase post-curing process: 80℃×2h→100℃×3h→120℃×4h, so that the interface between adjacent layers undergoes chemical bonding during the heating process, rather than physical superposition.

[0026] The performance tests were conducted as follows: After immersing the sample in a simulated waste lithium battery leachate (H2SO4 2mol / L + HCl 0.5mol / L + HF 0.1mol / L, 70℃) for 720 hours, the surface contact angle of the top layer was 112°, which is 31.8% higher than the 85° contact angle of conventional bisphenol A type epoxy vinyl ester resin fiberglass; the F⁻ permeability coefficient was 3.2×10⁻¹²m² / s, which is one order of magnitude lower than that of conventional fiberglass; and there was no delamination between the layers.

[0027] Example 2

[0028] This embodiment provides a method for applying the extraction tank of the present invention in the recycling of metals from waste lithium batteries, wherein the composition of the leachate is: Co²⁺ 28g / L, Li⁺ 4.2g / L, pH=1.2, F⁻=1200ppm, Cl⁻=3500ppm.

[0029] The extraction process is as follows: The leachate enters the mixing chamber 2 of the extraction tank of this invention and is mixed with P204 extractant at a ratio of O / A = 1:1. The extraction pH is 2.5, and the temperature is 25°C. The P204 extractant has a volume concentration of 20% and a saponification rate of 65%. After phase separation in the clarification chamber 3, the raffinate enters the next stage extraction tank and is mixed with P507 extractant at a ratio of O / A = 1.5:1. The extraction pH is 4.8, and the temperature is 35°C. The P507 extractant has a volume concentration of 25% and a saponification rate of 60%.

[0030] The supported organic phase was back-extracted with 2 mol / L H2SO4 to obtain a CoSO4 solution, in which Co²⁺ ≥ 48 g / L.

[0031] After 720 days of continuous operation, the extraction tank was inspected. The tank body and each inner lining layer showed no deformation, leakage or peeling, and the surface layer was smooth without corrosion pits.

[0032] Example 3: The difference from Example 1 is that this example provides a corrosion-resistant fiberglass extraction tank that utilizes the interlayer thermal stress generated by the gradient curing of a three-layer composite functional inner liner to enhance the structural strength of the tank.

[0033] In existing technologies, multi-layer fiberglass linings, due to the different coefficients of thermal expansion of the resin in each layer, generate interlayer thermal stress during the curing process. This is generally considered a defect leading to interface cracking, as seen in the interlayer delamination problem in the prior art patent with publication number CN2533934Y. However, the inventors of this application have discovered through research that when the three-layer composite lining is laid with a specific thickness ratio and a stepped heating curing process is used, the thermal stress between each layer can be precisely controlled within the elastic range, forming a pre-compression stress effect on the tank wall. This counteracts the tensile stress generated by changes in internal liquid pressure and temperature field during the operation of the extraction tank, significantly enhancing the crack resistance at the tank corners. This reverse-thinking design approach overcomes the technical prejudice of those skilled in the art that interlayer thermal stress can only be eliminated.

[0034] The specific structural design is as follows: the total wall thickness of the tank is 22mm, of which the fiberglass structure layer is 14mm thick, and the total thickness of the three-layer composite functional lining is 8mm. The designed thickness ratio of the bottom, middle, and top layers of the three-layer composite functional lining is 2:3:1, and the actual construction thickness deviation is controlled within ±0.2mm. The coefficients of thermal expansion of each resin system are as follows: the bottom layer is phenolic vinyl ester resin, with a coefficient of thermal expansion α1 of 28 × 10⁻⁶. -6 / ℃; the intermediate layer is an epoxy vinyl ester resin containing nano-SiO2, with a coefficient of thermal expansion α2 of 45×10. -6 / ℃; the surface layer is an epoxy vinyl ester resin containing PTFE micropowder, with a coefficient of thermal expansion α3 = 52 × 10⁻⁶. -6 / ℃. The stepped temperature curing process is as follows: bottom layer 80℃×2h → middle layer 100℃×3h → top layer 120℃×4h. During the curing process, each layer completes curing shrinkage at different temperatures. Due to the differences in thermal expansion coefficients and curing temperatures, a controllable thermal stress field is formed between the layers. Since the bottom layer has the smallest thermal expansion coefficient and the top layer has the largest, during the post-curing cooling process, the shrinkage of the top layer is constrained by the middle and bottom layers, resulting in tensile stress, while the bottom layer is subjected to corresponding compressive stress. By selecting the thickness ratio and stepped curing temperature, the tensile stress of the top layer is always kept below its allowable tensile stress, ensuring that the top layer does not crack during service. At the same time, the compressive stress of the bottom layer is transferred through the fiberglass structure layer, keeping the tank wall panel in a pre-compressed state, effectively offsetting the tensile stress generated during service. Each layer completes volume shrinkage sequentially within its respective curing temperature window, which not only avoids interlayer stress accumulation but also achieves the dual effects of interface molecular-level chemical bonding and structural reinforcement. Comparative experiments verified that after 720 hours of operation under the same internal pressure of 0.3 MPa and a temperature cycle of 25°C to 70°C and back to 25°C for 24 hours, the conventional single-layer fiberglass tank control group developed microcracks at the corners, with a crack depth ≥0.5 mm and a length between 5 and 15 mm. In contrast, the experimental group tank using a three-layer composite lining combined with a stepped curing process, with the same wall thickness and geometric dimensions as the control group, showed no structural damage, no cracks at the corners, and surface strain gauge monitoring data showed that the maximum principal strain in the experimental group was 38.8% lower than that in the control group, and the overall bending stiffness of the tank was increased by 25%. The experiments confirm that the three-layer composite lining combined with the stepped curing process of this invention significantly improves the crack resistance and overall structural stability of the tank.

[0035] The specific verification is as follows: A comparative experiment was conducted using tanks with identical geometric dimensions. Each tank had a size of 2000mm × 1500mm × 1800mm, with a radius of curvature R = 50mm. The control group consisted of a conventional single-layer fiberglass tank with a wall thickness of 22mm, prepared with bisphenol A type epoxy vinyl ester resin and cured using a conventional process. The experimental group used the tank described in this invention, also with a total wall thickness of 22mm, composed of a 14mm fiberglass structural layer and an 8mm three-layer composite inner lining, and formed using a stepped curing process. The experimental results are shown in the table below:

[0036] The experimental results show that the experimental group outperformed the control group in terms of stress, strain, crack resistance, and stiffness. The mechanism lies in the fact that during the stepped curing and cooling process, the three inner lining layers generate a controllable thermal stress field due to the difference in their thermal expansion coefficients. The bottom layer is compressed due to the greater shrinkage of the surface and intermediate layers, generating compressive stress that is transferred to the fiberglass structural layer, resulting in a pre-compressed state for the tank wall panels. The tensile stress of the surface layer is controlled to remain below the allowable value by a thickness ratio of 2:3:1, preventing cracking. This pre-compressive stress effectively counteracts the tensile stress generated by the internal pressure during service, thereby significantly reducing the principal stress at corners, decreasing strain, and improving crack resistance and overall stiffness.

[0037] The pre-stress-enhanced structure of this embodiment uses the same material system and stepped curing process as the three-layer composite functional liner in Embodiment 1. In other words, the stepped heating and curing process in Embodiment 1 plays two roles simultaneously: first, by curing each layer sequentially to form a chemically bonded transition layer, it avoids interface cracking, mainly solving the interlayer delamination problem existing in the prior art patent with publication number CN2533934Y; second, during the cooling process, the three-layer liner generates a controllable thermal stress field due to the difference in thermal expansion coefficients, causing compressive stress to form in the bottom layer and transferring it to the tank wall panel, so that the wall panel as a whole is in a pre-compressed state, thereby enhancing the crack resistance and overall rigidity of the tank, mainly solving the stress concentration cracking problem at the junction of the side plate and the bottom plate existing in the prior art patent with publication number CN202898488U. This pre-stress effect is achieved in conjunction with the thickness ratio control, i.e., bottom layer: intermediate layer: top layer = 2:3:1, and the selection of stepped curing temperature, without the need for additional processes or structures.

[0038] In this embodiment, the stepped temperature curing process achieves two effects simultaneously: 1. Through resin chemical crosslinking and interfacial diffusion, a chemically bonded transition layer is formed between each layer, preventing interfacial delamination during service due to differences in thermal expansion coefficients; 2. Through a gradient design of thermal expansion coefficients, α1 = 28 × 10⁻⁶. -6 / ℃<α2=45×10 -6 / ℃<α3=52×10 -6 The temperature is increased by ℃, causing the bottom layer to be compressed and the top layer to be tensile during the cooling process. The compressive stress in the bottom layer is transferred to the tank wall panels, forming a controllable pre-compression stress effect, thereby improving the overall stiffness and crack resistance of the tank. These two effects are achieved synergistically by the same stepped heating and curing process, without the need for additional processes or structures.

[0039] Example 4: The difference from Example 1 is that this example provides a corrosion-resistant fiberglass extraction tank sealing structure that uses flange face compression creep defects to compensate for the aging shrinkage of the sealing gasket, and is applicable to the upper flange connection surface of the extraction tank body described in Example 1.

[0040] The flange at the top of the FRP extraction tank is used to install the tank cover and achieve an airtight seal. In existing technology, the flange face typically has a flat structure. A seal is achieved by placing an acid-resistant rubber gasket between the two flange faces and applying bolt preload to compress and deform the gasket. However, this structure has two independent mechanical defects. First, there is the compression creep defect of the FRP flange face. FRP is a resin-based composite material, and its compressive strength is much lower than that of metal materials. Under bolt preload, the resin matrix of the flange face inevitably develops local indentations in the contact area with the bolt gasket, initiating compression creep and causing irreversible compression thinning of the flange face thickness by 0.1~0.3mm in the early stages of service. This phenomenon is listed as a typical structural deformation risk or a long-term performance degradation behavior that requires key control in FRP equipment design manuals, and is usually avoided by using metal inserts or strictly controlling the preload. Second, there is the aging and shrinkage defect of the rubber gasket. The extraction tank is exposed to a gaseous environment containing volatile acid mists of HF and HCl for extended periods, with operating temperatures ranging from 15 to 45°C, and locally reaching 60°C. Under the combined effects of acidic media and heat and oxygen, the acid-resistant rubber sealing layer of the flange undergoes cross-linking network breakage and plasticizer volatilization, gradually resulting in permanent compression deformation with a volume shrinkage rate of 15% to 25%. This leads to a decrease in contact stress at the sealing surface, ultimately causing bolt loosening and gas leakage. Both of these defects are considered undesirable phenomena in existing technologies and are typically addressed using the following methods: for crushing defects, they are suppressed by embedding metal gaskets or using high-compression-strength resins; for gasket aging and shrinkage defects, they are maintained by periodically retightening the bolts or replacing the gaskets.

[0041] This embodiment provides a fiberglass flange sealing structure with a creep compensation groove, such as... Figure 2 As shown. On the flat sealing surface of the upper flange 10 of the extraction tank body 1, an annular groove serving as a compensation groove 11 is formed in the annular area covered by the sealing gasket. In this structure, the nominal width of the sealing gasket is based on its cross-sectional width in its free state; the width of the compensation groove is 60%~80% of the nominal width of the gasket, and the depth of the compensation groove H=0.5~1.0mm. The compensation groove is integrally formed by machining after the flange is formed and demolded, and there are no fiber cutting or delamination defects at the bottom of the groove. The inner wall of the compensation groove is integrally laminated with the tank body of fiberglass material, without adhesive interface. The bottom surface of the compensation groove is a plane parallel to the flange surface, and the two side walls of the compensation groove are transitioned to the bottom surface by an arc 12 with R=2~3mm. The setting of the compensation groove makes the cross-section of the fiberglass in this area thinner than other areas of the flange, so that this area will generate compressive creep preferentially than other areas under the action of bolt preload.

[0042] The sealing gasket adopts a double-layer composite structure. The lower layer is a soft acid-resistant rubber layer 14 that is attached to the compensation groove, with an original thickness of T=2~3mm and a hardness of 50~60 Shore A. The upper layer is a hard PTFE annular tooth 15 that is vulcanized and bonded to the surface of the rubber layer. The tooth height is 1.0~1.5mm, of which 0.3~0.5mm is embedded in the rubber layer, and the rest is flush with the rubber surface in the initial state. The tooth width is 30%~40% of the gasket width.

[0043] The following relationships exist between the depth H of the compensation groove, the original thickness T of the rubber layer, the compressive creep ΔH of the fiberglass in the compensation groove area, and the aging shrinkage ΔT of the rubber layer: Assume the compressive creep of the fiberglass in the compensation groove area under bolt preload is represented by a decrease in the groove depth, denoted as ΔH, which is measured to be 10%~20% of H, i.e., ΔH = 0.05~0.20 mm; simultaneously, the lower soft acid-resistant rubber layer, after undergoing an equivalent of 24 months of service within the gasket's design service life, experiences a permanent compression shrinkage ΔT, which is measured to be 15%~25% of T, i.e., ΔT = 0.30~0.75 mm; the thickness variation of the PTFE teeth in the double-layer composite gasket is negligible, therefore the overall gasket thickness reduction is approximately equal to ΔT; H and T satisfy the initial size ratio relationship: H = β.T, where β = 0.2~0.4; that is, H = 0.5~1.0mm corresponds to T = 2~3mm; the effective compensation ratio provided by the compensation groove is determined by the value of ΔH / ΔT. After optimization, when H = 0.8mm and T = 2.5mm, ΔH ≈ 0.18mm, ΔT ≈ 0.48mm, and ΔH / ΔT ≈ 0.375. That is, the creep stroke of the compensation groove can compensate for about 30%~40% of the shrinkage of rubber due to aging, so that the contact stress of the sealing surface is always maintained above the effective sealing threshold of 2.5MPa, while avoiding excessive crushing that could lead to flange structural damage. Among them, H = 0.8mm and T = 2.5mm is the preferred implementation scheme of this structure, which can achieve optimal compensation matching under operating conditions of 15~60℃ and HF / HCl acid mist environment.

[0044] One of the mechanisms of operation in this embodiment is a timing misalignment compensation mechanism. Six months after the extraction tank is put into operation, the bolt preload first acts on the compensation tank area, inducing compression creep of the fiberglass, causing the tank depth to gradually decrease. After the compensation tank becomes shallower, the compression allowance originally absorbed by the compensation tank is released, and the actual compression of the sealing gasket increases. At this stage, the seal is mainly provided by the elastic deformation of the gasket itself to provide contact stress. Due to the compression creep of the fiberglass in the compensation tank area, the bottom of the tank bulges upward. Under the condition that the bolt preload remains unchanged, the sealing gasket is forced to generate additional compression, thereby increasing the contact stress from the initial 3.1 MPa to 3.2 MPa. In the middle of service (6-24 months), the rubber gasket gradually ages and shrinks in the acid mist and heat-oxygen environment, and the sealing contact stress begins to decrease. At this time, since the compensation tank has released part of the compression allowance through creep in the early stage, this pre-compression stroke just offsets the rubber aging shrinkage, keeping the total compression of the sealing surface within the effective range, keeping the contact stress above the critical threshold of 2.5 MPa, and avoiding seal failure due to gasket aging. The second mechanism of action in this embodiment is the labyrinth seal enhancement mechanism. Under the preload, the PTFE protrusions are compressed together with the rubber layer, forming a labyrinth seal path at the three interfaces of fiberglass-rubber-PTFE. When the rubber ages and shrinks, the PTFE protrusions become relatively prominent due to the weakened rubber support, but still maintain contact with the rubber layer, further enhancing the tooth shape effect of the labyrinth seal. This increases the penetration path length of gaseous corrosive media such as HF and HCl, and increases leakage resistance. In other words, the traditional defect of gasket aging and shrinkage is actually enhanced in this case by strengthening the labyrinth seal effect.

[0045] To verify the technical effectiveness of this embodiment, accelerated aging comparative experiments were conducted using fiberglass flange specimens of the same size. The control group used a conventional flat flange with a flat rubber gasket, with bolt torque applied according to the standard value, without a compensation groove. The experimental group used a flange with a compensation groove and a double-layer composite sealing gasket, where the compensation groove depth was 0.8 mm, the gasket rubber layer thickness was 2.5 mm, the PTFE tooth height was 1.2 mm, and the bolt torque was the same. Both groups had the same bolt torque. Due to the reduced flange stiffness in the compensation groove area, the initial contact stress in the experimental group was slightly lower than that in the control group. This is a predictable deviation caused by the reduced local stiffness of the flange in the compensation groove area under the same preload torque level. The experiment was conducted in an 80℃ constant temperature chamber, with a continuous airflow containing 500 ppm HF vapor. The total duration was set to 2000 hours to simulate the actual working environment of 24 months of service. The sealing surface contact stress and gas leakage rate were measured every 500 hours.

[0046] The accelerated aging test data are shown in the table below:

[0047] Results Analysis: In the control group, the contact stress continuously decreased, dropping below 1.0 MPa after 2000 hours, which was below the effective sealing threshold. The leakage rate reached 1.56 mL / min·m, exceeding the allowable value by more than 15 times, thus indicating sealing failure. In the experimental group, the contact stress increased from 3.1 MPa to 3.2 MPa within 0–500 hours. This was due to compression creep of the fiberglass in the compensation groove area, causing the bottom of the compensation groove to shift upwards. This slightly increased the actual compression of the sealing gasket while maintaining the initial bolt preload, resulting in a temporary increase in contact stress. Subsequently, the stress gradually decreased with rubber aging, but remained at 2.7 MPa after 2000 hours, far exceeding the effective sealing threshold. The leakage rate remained between 0.02 and 0.04 mL / min·m throughout the process, with no sealing failure observed.

[0048] The flange sectioning test after the accelerated aging test showed that: the depth of the compensation groove in the experimental group decreased from the initial 0.8 mm to 0.62 mm, and the compression creep was 0.18 mm; the thickness of the rubber gasket decreased from 2.5 mm to 2.02 mm, and the aging shrinkage was 0.48 mm; the creep compensation accounted for 37.5% of the aging shrinkage, and the experiment confirmed that the compensation mechanism was operating effectively.

[0049] This embodiment addresses two traditional defects—compression creep of the fiberglass flange face under bolt preload and aging shrinkage of the rubber gasket in an acidic, hot, and oxygen-rich environment—by processing them in stages and sequentially. This allows the former to occur earlier in time and provides space for travel, so that when the latter occurs, the compression allowance released in advance by the compensation groove automatically compensates for the gasket shrinkage.

[0050] Compared with existing technologies, this embodiment has the following outstanding advantages: First, it requires no regular maintenance. Conventional technologies require shutdown to retighten bolts or replace gaskets. This embodiment utilizes the inherent creep characteristics of fiberglass material to achieve self-maintaining of the sealing pressure. Within an equivalent 24-month service life, no manual retightening of bolts or replacement of gaskets is required to maintain sealing effectiveness. This period has been verified by a 2000-hour accelerated aging test with HF vapor, corresponding to the typical service life under actual industrial conditions of 15~60℃. Second, it turns disadvantages into advantages. The structural failure mode of fiberglass flange face crushing, which is warned against by all design specifications and construction standards, is controlled within the expected trajectory through a compensation groove thinning design, transforming it into a functional element that achieves self-compensating sealing. Third, it breaks through technical biases with reverse thinking. In existing technologies, flange face crushing and gasket aging are treated as two independent problems. This embodiment creatively links the two, utilizing their time-scale misalignment to achieve self-compensating sealing, providing a completely new direction for the sealing design of fiberglass equipment.

[0051] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. The application of a corrosion-resistant fiberglass extraction tank in the recycling of metals from waste lithium batteries, characterized in that, Includes the following steps: (1) The waste lithium batteries are crushed, sorted and acid-leached to obtain acidic leachate; (2) The leachate is solvent extracted in the corrosion-resistant fiberglass extraction tank to extract and separate valuable metal elements; (3) The supported organic phase was back-extracted to obtain a metal salt solution; The corrosion-resistant fiberglass extraction tank includes a tank body made of integral laminated fiberglass material. The tank body is equipped with a mixing chamber and a clarification chamber, which are separated by a partition plate. The corners of the tank body adopt an arc transition structure, and the outer wall is equipped with reinforcing ribs. The surface of the tank body that comes into contact with the corrosive medium is equipped with a three-layer composite functional lining layer, which is composed of a bottom layer, an intermediate layer, and a top layer from the inside out. The bottom layer is a phenolic vinyl ester resin fiberglass layer, the intermediate layer is a bisphenol A type epoxy vinyl ester resin fiberglass layer containing nano-SiO2, and the top layer is a bisphenol A type epoxy vinyl ester resin fiberglass layer containing PTFE micro powder.

2. The application of the corrosion-resistant fiberglass extraction tank according to claim 1 in the recycling of metals from waste lithium batteries, characterized in that, The thickness of the bottom layer is 2-3 mm, the thickness of the middle layer is 3-5 mm, the thickness of the top layer is 1-2 mm, and the total thickness of the three layers is 6-10 mm; the nano-SiO2 particles have a diameter of 20-50 nm and are added at 5%-10% of the resin mass; the PTFE micro powder has a particle size ≤10 μm, is surface modified with a silane coupling agent, and is added at 3%-8% of the resin mass.

3. The application of the corrosion-resistant fiberglass extraction tank according to claim 2 in the recycling of metals from waste lithium batteries, characterized in that, After the three-layer composite functional lining is laid, a stepped heating and curing process is adopted: first, it is cured at 80℃ for 2 hours, then the temperature is raised to 100℃ for 3 hours, and finally the temperature is raised to 120℃ for 4 hours, so that a chemically bonded transition layer is formed between each layer.

4. The application of the corrosion-resistant fiberglass extraction tank according to claim 3 in the recycling of metals from waste lithium batteries, characterized in that, The upper flange of the tank is provided with a flange sealing system, including a sealing gasket and an acid mist baffle; the sealing gasket is set on the flange sealing surface to achieve initial sealing of the flange connection surface; the acid mist baffle has a double-layer structure, the inner layer is phenolic vinyl ester resin fiberglass, and the outer layer is an acid-resistant rubber sealing layer, which is fixed to the inner layer surface by adhesive.

5. The application of the corrosion-resistant fiberglass extraction tank according to claim 4 in the recycling of metals from waste lithium batteries, characterized in that, The pH of the leachate in step (2) is 1.0~2.0, and it contains F. - 1000~5000ppm, Cl - 2000~10000ppm; the solvent extraction uses one or more of P204 or P507 extractants, and the operating temperature during the extraction process is 15~45℃.

6. The application of the corrosion-resistant fiberglass extraction tank according to claim 5 in the recycling of metals from waste lithium batteries, characterized in that, The valuable metal element is selected from one or more of cobalt, nickel, manganese, and lithium.

7. The application of the corrosion-resistant fiberglass extraction tank according to claim 6 in the recycling of metals from waste lithium batteries, characterized in that, The clarification chamber is equipped with an adjustable light phase weir at the top and a heavy phase outlet at the bottom; the mixing chamber is equipped with a stirring device, and the stirring shaft and impeller are covered with a three-layer composite functional inner lining layer that is the same as the inner lining layer of the tank.

Citation Information

Patent Citations

  • Comprehensive recovery method of waste lithium battery

    CN114892005A

  • Pure glass fiber reinforced plastic extraction settling pond

    CN202898487U

  • Reinforced glass reinforced plastic extraction clarification tank

    CN202898488U

  • Extraction device for wet recovery of waste lithium batteries

    CN220914333U

  • Extraction tank for improved rare-earth separation

    CN2533934Y